Juvenile Coffee Leaves Acclimated to Low Light Are Unable to Cope with a Moderate Light Increase - Campa, Claudine; Urban, Laurent; Mondolot, Laurence; Fabre, Denis; Roques, Sandrine; Lizzi, Yves; Aarrouf, Jawad; Doulbeau, Sylvie; Breitler, Jean-Christophe; Letrez, Céline; Toniutti, Lucile; Bertrand, Benoit; et al. (Frontiers in Plant Science, 2017)
The understorey origin of coffee trees and the strong plasticity of Coffea arabica leaves in relation to contrasting light environments have been largely shown. The adaptability of coffee leaves to changes in light was tested under controlled conditions by increasing the illumination rate on C. arabica var. Naryelis seedlings acclimated to low light conditions and observing leaf responses at three different developmental stages (juvenile, growing and mature). Only mature leaves proved capable of adapting to new light conditions. In these leaves, different major mechanisms were found to contribute to maintaining a good photosynthetic level. With increased illumination, a high photosynthetic response was conserved thanks to fast nitrogen remobilization, as indicated by SPAD values and the photorespiration rate. Efficient photoprotection was accompanied by a great ability to export sucrose, which prevented excessive inhibition of the Calvin cycle by hexose accumulation. In contrast, in younger leaves, increased illumination caused photodamage, observable even after nine days of treatment. One major finding was that young coffee leaves rely on the accumulation of chlorogenic acids, powerful antioxidant phenolic compounds, to deal with the accumulation of reactive oxygen species rather than on antioxidant enzymes. Due to a lack of efficient photoprotection, a poor ability to export sucrose and inadequate antioxidant protection, younger leaves seemed to be unable to cope with increased illumination. In these leaves, an absence of induced antioxidant enzyme activity was accompanied, in growing leaves, by an absence of antioxidant synthesis or, in juvenile leaves, inefficient synthesis of flavonoids because located in some epidermis cells. These observations showed that coffee leaves, at the beginning of their development, are not equipped to withstand quick switches to higher light levels. Our results confirm that coffee trees, even selected for full sunlight conditions, remain shade plants possessing leaves able to adapt to higher light levels only when mature.